HUBUNGAN ANTARA TINGGI HAK DAN LAMA PEMAKAIAN HIGH HEELS DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PRAMUGARI MASKAPAI X AIR - Reza Almayda, (2022)
Low back pain is a discomfort in the lower back area in the form of pain. Flight attendants when on duty use high heels, this results in a change in the fulcrum when walking. Problems occur when wearing high heels for a long period of time, the lumbar muscles will be more attractive, causing muscle shortening and pain in the lower back. The purpose of writing this scientific paper is to find out the relationship between the height of the right and the length of use of high heels with complaints of low back pain in airline x air flight attendants. The parameter used to measure complaints of low back pain is NRS. This study uses correlation research with a cross-sectional approach. Based on the results of SPSS 25 obtained Asymp.Sig(2-tailed) = 0,000 there is a relationship between complaints of low back pain on flying hours in 24 hours and working period. SPSS 25 results obtained Asymp.Sig(2-tailed) = 0,164 where greater than (p<0,05) there is no relationship between the height of high heels with low back pain